Inducer of heme oxygenase‐1 cobalt protoporphyrin accelerates autophagy and suppresses oxidative damages during lipopolysaccharide treatment in rat liver. Issue 1 (11th December 2012) - Unuma, Kana; Aki, Toshihiko; Matsuda, Seiji; Funakoshi, Takeshi; Yoshida, Ken‐ichi; Uemura, Koichi
<x xml:space="preserve">Abstract</x> Aim: Mitochondrial damage and subsequent oxidative stresses play important roles in the pathogenesis of sepsis‐induced organ failure. Recently, autophagy, the major degradation pathway involved in mitochondrial quality control, was reported as a cellular adaptive response to oxidative stresses. The aim of the present study was to elucidate the molecular mechanism that underlies hepatic damage during lipopolysaccharide (LPS) treatment. We also try to determine if the damage can be attenuated by administration of cobalt protoporphyrin (CoPP), a potent heme oxygenase‐1 (HO‐1) inducer. Methods: Five‐week‐old male Sprague–Dawley rats were injected i.p. with 15 mg/kg LPS. To determine if hepatic damage following LPS administration can be attenuated by HO‐1, CoPP was injected s.c. for 4 days consecutively at 24‐h intervals. After treatment with LPS, the liver was obtained and analyzed. Results: A large reduction in liver mitochondrial protein and induction of autophagy were observed in LPS‐treated rats. Electron microscopic and immunohistochemical analyses demonstrated autophagic vacuoles in LPS‐treated rat liver. Oxidative stress markers (4‐hydroxy‐2‐nonenal and 8‐hydroxy‐2′‐deoxyguanosine) were increased in LPS‐treated animals; CoPP treatment ablated these alterations. An inhibitor for the opening of mitochondrial permeability transition pore, cyclosporine A, suppressed oxidative stress as well as liver damage during LPS administration. CoPP promoted autophagy and prevented rats from liver damage during LPS administration. Conclusion: HO‐1 promotes autophagy and elimination of damaged mitochondria thereby repressing oxidative stress in LPS‐treated rat liver, revealing a novel mechanism for protection by HO‐1 against septic liver damage.